Rolling Away the Stone : Mary Baker Eddy's Challenge to Materialism - Gottschalk, Stephen (Book collections on Project MUSE., 2006)
"Rolling Away the Stone is a richly detailed account of the last two decades of the life of Mary Baker Eddy, a major religious thinker whose character and achievement are just beginning to be understood. This first book-length discussion of Eddy to make full use of the resources of The Mary Baker Eddy Collection in Boston focuses as no other previous book has on her long-range legacy as a Christian thinker, specifically her challenge to the materialism that - in changing forms - continues to threaten religious belief and practice in our time."--Jacket